Scaling of Primate Forearm Muscle Architecture as It Relates to Locomotion and Posture. Issue 3 (8th February 2018) - Leischner, Carissa L.; Crouch, Michael; Allen, Kari L.; Marchi, Damiano; Pastor, Francisco; Hartstone‐Rose, Adam
ABSTRACT: It has been previously proposed that distal humerus morphology may reflect the locomotor pattern and substrate preferred by different primates. However, relationships between these behaviors and the morphological capabilities of muscles originating on these osteological structures have not been fully explored. Here, we present data about forearm muscle architecture in a sample of 44 primate species (N = 55 specimens): 9 strepsirrhines, 15 platyrrhines, and 20 catarrhines. The sample includes all major locomotor and substrate use groups. We isolated each antebrachial muscle and categorized them into functional groups: wrist and digital extensors and flexors, antebrachial mm. that do not cross the wrist, and functional combinations thereof. Muscle mass, physiological cross‐sectional area (PCSA), reduced PCSA (RPCSA), and fiber length (FL) are examined in the context of higher taxonomic group, as well as locomotor/postural and substrate preferences. Results show that muscle masses, PCSA, and RPCSA scale with positive allometry while FL scales with isometry indicating that larger primates have relatively stronger, but neither faster nor more flexible, forearms across the sample. When accounting for variation in body size, we found no statistically significant difference in architecture among higher taxonomic groups or locomotor/postural groups. However, we found that arboreal primates have significantly greater FL than terrestrial ones, suggesting that these species are adapted for greater speed and/or flexibility in the trees. These data may affect our interpretation of the mechanisms for variation in humeral morphology and provide information for refining biomechanical models of joint stress and movement in extant and fossil primates. Anat Rec, 301:484–495, 2018. © 2018 Wiley Periodicals, Inc.